Freedom is Everybody's Job!: The Crime of the Government Against the Negro People - Crockett, George W., Jr. (National Non-Partisan Committee to Defend the Rights of the 12 Communist Leaders, 1949)
Freedom is Everybody's Job!: The Crime of the Government Against the Negro People By George W. Crockett. Jr. This booklet is a portion of Crockett's summation to the jury in the 1948 trial of eleven communist leaders who were tried under the Smith Act for organizing as a Communist party. Crockett, originally from Honda, was a crusading Civil Rights lawyer. He was also a Representative from Michigan.
Freedom is Everybody's Job!: The Crime of the Government Against the Negro People By George W. Crockett. Jr This booklet is a portion of Crockett's summation to the jury in the 1948 trial of eleven communist leaders who were tried under the Smith Act for organizing as a Communist party. Crockett, originally from Honda, was a crusading Civil Rights lawyer. He was also a Representative from Michigan N12975 $25.00 1940 U-AfAmPaper UUID: 8A29D1B4-320B-4D35-A7B6-6F918D2CB37F Digitized by Dallas Suttles, 3/6/2016. Valdosta State University Archives and Special Collections, 2016. **Contact:** dasuttles@valdsota.edu
Keywords: Communism > United States; African Americans